Nemerteans in an Irish marine reserve: synopsis of current and historical records. (5th October 2015) - Trowbridge, Cynthia D.; Hiebert, Laurel S.; Junoy, Juan; Little, Colin; Stirling, Penny; Dlouhy-Massengale, Brittney; McAllen, Rob
Abstract : The under-rock guild of nemerteans from Lough Hyne, south-west Ireland was recorded during a long-term benthic survey of the marine reserve. From 2004 to 2014, common nemerteans were recorded annually in late summer for ten historical monitoring sites (each 10 m of shoreline); more comprehensive surveys were completed in 2012 (4126 low-intertidal to shallow-subtidal rocks were turned) and 2014 (1289 rocks turned) with supplementary information in 2015. The bootlace worm, Lineus longissimus, was the most abundant nemertean species. It was significantly more abundant at the extremely shallow East Castle site than the other nine sites; peak populations (across all ten sites) occurred in 2012. The Lusitanian nemertean Paradrepanophorus crassus was abundant after 2007. To date, 13 nemertean species were recorded with numerous new records for the lough, including Tubulanus annulatus, Micrura purpurea, Ramphogordius sanguineus, Micrella rufa and Emplectonema gracile . Three additional nemertean species were previously recorded, indicating that at least 16 species occur in the lough. Given the low densities and paucity of comprehensive earlier records, we are not able to ascertain definitely whether these species are new incursions or if sparsely distributed residents have increased.